2021
DOI: 10.1002/jmv.26848
|View full text |Cite
|
Sign up to set email alerts
|

Clinical characteristics of 4499 COVID‐19 patients in Africa: A meta‐analysis

Abstract: The novel coronavirus disease-2019 (COVID-19) pandemic that started in December 2019 has affected over 95 million people and killed over 2 million people as of January 19, 2021. While more studies are published to help us understand the virus, there is a dearth of studies on the clinical characteristics and associated outcomes of the severe acute respiratory syndrome coronavirus 2 on the African continent. We evaluated evidence from previous studies in Africa available in six databases between January 1 and Oc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
22
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 29 publications
4
22
1
Order By: Relevance
“…Mortality was 14% in patients aged 60 or more, and 26% in people with severe respiratory signs on admission. Although no comparisons can be made between hospitals in different countries with different hospitalization practices and levels of care, these figures are consistent with what has been described elsewhere (Lv et al, 2020;Olumade and Uzairue, 2021;Singer et al, 2020) and strongly suggest that COVID-19 is at least as serious in Africa as it is in other continents. (Boulle et al, 2020;Elimian et al, 2020;Kirenga et al, 2020;Nachega et al, 2020) If the reported death toll from COVID-19 is lower in Africa than in Europe or the USA, (Chilimuri et al, 2020;Galloway et al, 2020;Rossi et al, 2020;Zhou et al, 2020) it is probably not because the disease is less lethal in Africa.…”
Section: J O U R N a L P R E -P R O O Fsupporting
confidence: 85%
See 1 more Smart Citation
“…Mortality was 14% in patients aged 60 or more, and 26% in people with severe respiratory signs on admission. Although no comparisons can be made between hospitals in different countries with different hospitalization practices and levels of care, these figures are consistent with what has been described elsewhere (Lv et al, 2020;Olumade and Uzairue, 2021;Singer et al, 2020) and strongly suggest that COVID-19 is at least as serious in Africa as it is in other continents. (Boulle et al, 2020;Elimian et al, 2020;Kirenga et al, 2020;Nachega et al, 2020) If the reported death toll from COVID-19 is lower in Africa than in Europe or the USA, (Chilimuri et al, 2020;Galloway et al, 2020;Rossi et al, 2020;Zhou et al, 2020) it is probably not because the disease is less lethal in Africa.…”
Section: J O U R N a L P R E -P R O O Fsupporting
confidence: 85%
“…This reasoning is also compatible with the 2.8%, 9.2% and 13.2% mortality rates reported from retrospective population or hospital-based cohorts in South-Africa, Nigeria and the Democratic Republic of the Congo (Boulle et al, 2020;Elimian et al, 2020;Nachega et al, 2020) as well as the 5.6% of an African meta analysis. (Olumade and Uzairue, 2021) In the present study, the predominant clinical presentation was respiratory. Digestive signs and general signs, headaches, myalgia and asthenia were nevertheless quite frequent, as J o u r n a l P r e -p r o o f was a lack of taste and smell.…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 46%
“…In the current study, the main clinical symptoms of COVID-19 patients were fever (56%), cough (48%), muscle and body pain (38%), weakness and lethargy (32%), and dyspnea (26%), while minor symptoms included runny nose (10%), diarrhea (7%), and tachycardia (5%). These findings are more or less consistent with meta-analysis studies performed by Li et al (17) , Zhu et al (18) , Li et al (19) , Qiu et al (20) , Pormohammad et al (21) and Olumade et al (22) , indicating that individuals with clinical features linked to the disease should be monitored closely.…”
Section: Discussionsupporting
confidence: 85%
“…In Africa, there is little information available about the clinical characteristics and prognosis of COVID-19-infected patients [4][5][6][7][8]. Global mortality rates range from 4% to 5.6% [4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…In Africa, there is little information available about the clinical characteristics and prognosis of COVID-19-infected patients [4][5][6][7][8]. Global mortality rates range from 4% to 5.6% [4][5][6][7][8]. In-hospital mortality is high, in particular for patients with acute respiratory distress requiring ICU admission and mechanical ventilation [4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%